Pengembangan Kurikulum Tahfizh Al Qur'an Di Pondok Pesantren Al Qur'an - Yasri, Hayyun Lathifaty (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This reseach was aims to 1) develop a curricula document which have fulfill the expediency criteria for An Nur Qur?anic Islamic Boarding School of Malang, 2) know the expediency of the product that developed for An Nur Qur?anic Islamic Boarding School of Malang. The curriculum development in this reseach was used Beachamp Development Model which deliver: 1) the curricula document which have fulfill the expediency criteria to be applied in the An Nur Qur?anic Islamic Boarding School of Malang. 2) The application of the developed curriculum was been responsed good by the user. The distinction of this developed curricula with another curricula is the content of the developed curricula were cover the students need which include islamic sciences, qur?anic sciences, and sciences. In othes side, this curricula was developed the simmulation in its evaluation system. This simmulation was developed for testing students automatical memorize of Al Qur?an. So, the suggestion for this research is 1) adding the facility for supporting the student learning and memorizing. 2) The organizator should strengthen the student discipline system, especially in order to memorize the Holy Qur?an. 3) The Procurement of montly evaluation which was scheduled to evaluate student memorize progress.